Microplastics divert carbon flow in anaerobic digestion: a meta-analysis reveals product-specific effects - Cong Jiang; Ruirui Pang; Wenyue Wang; Bing Xie; Min Zhan; Jingyang Luo; Yinglong Su (Bioresource Technology, 2026)

Benchmark testing for 2H neutron cross section calculated using Faddeev equation - Huanyu Zhang; Haicheng Wu; Ruirui Xu; Ping Liu; Xiaofei Wu; Xiaodong Sun; Danyang Pang (Annals of Nuclear Energy, 2025)

Effect of alkaline-thermal pretreatment on biodegradable plastics degradation and dissemination of antibiotic resistance genes in co-compost system - Wenyue Wang; Jianping Tao; Ruirui Pang; Linjie Zhang; Yuchen Zhang; Yinglong Su; Weiying Li; Seungkwan Hong; Hyunook Kim; Min Zhan; Bing Xie (Journal of Hazardous Materials, 2025)

Involvement of the miR156/SPLs/NLP7 modules in plant lateral root development and nitrogen uptake - Ruirui Xu; Peng Wang; Yunning Pang; Huilian Liu; Tianpeng Zhang; Ying Li; Shizhong Zhang (Planta, 2025)

Depositional evolution of nearshore fringing reefs in the Changpi region, Hainan Island: assessing the impact of siliciclastic influx on reef development - Maosong Ye; Lijuan Shao; Ruirui Song; Weihua Liao; Qiaozhu Pang; Hongfei Xu (Frontiers in Marine Science, 2025)
Nearshore fringing reefs have been shown to establish and accrete within sediment-laden coastal environments over millennial timescales. However, the mechanisms governing the evolution of turbid-water reefs remain inadequately understood. This study focuses on a fringing reef in the Changpi (CP) region along the eastern coast of Hainan Island, China. Sedimentological and geochronological analyses of four drill cores provided the first comprehensive growth history for this marginal reef setting through a systematic reconstruction of its developmental chronology, architectural framework, and ecological characteristics. Radiocarbon dating reveals reef initiated at about 7,400 cal yr BP and ceased accretion after 4,000 cal yr BP. By integrating core observations, thin-section petrography, and X-ray diffraction results, five distinct lithofacies were identified. These lithofacies exhibit varying degrees of mixing between siliciclastic and carbonate components, revealing that the reef system was periodically influenced by terrigenous siliciclastic input. The vertical accretion of the CP reef underwent three primary stages: (1) colonization stage (7,400-6,400 cal yr BP), characterized by well-preserved coral assemblages in high-energy, clear-water conditions with relatively low accretion rates (ca 0.35 mm/yr) and gradual coral diversification; (2) turbid stage (6,400-5,500 cal yr BP), marked by rapid terrigenous clastic deposition that produced persistent turbidity, leading to accelerated accretion rates (up to 6.29 mm/yr) and reduced coral diversity; and (3) stabilization stage (5,500-4,000 cal yr BP), during which stabilized siliciclastic input restored clear-water conditions, supporting renewed coral growth at moderate accretion rates (ca 2.70 mm/yr). This case study demonstrates that terrestrial sediment fluxes can exert a greater influence on nearshore reef trajectories than sea-level changes, particularly in regions or periods characterized by high sediment input. As suggested by the findings, this underscores the necessity of integrated coastal zone management strategies aimed at reducing agricultural runoff and controlling construction sediment to enhance reef resilience.

Dynamic responses of the inter-microbial synergism and thermodynamic conditions attribute to the inhibition-and-relief effects of chitosan towards anaerobic digestion - Ru Fang; Xueting Wang; Zhibang Han; Ruirui Pang; Dong Wu; Jun Tai; Chuang Ouyang; Min Zhan; Hyunook Kim; Bing Xie; Yinglong Su (Water Research, 2024)

Exposure modes determined the effects of nanomaterials on antibiotic resistance genes: The different roles of oxidative stress and quorum sensing - Xueting Wang; Qirui Chen; Ruirui Pang; Congyan Zhang; Guangchen Huang; Zhibang Han; Yinglong Su (Environmental Pollution, 2024)

Entry pathways determined the effects of MPs on sludge anaerobic digestion system: The views of methane production and antibiotic resistance genes fates - Xueting Wang; Guangchen Huang; Qirui Chen; Ruirui Pang; Zhibang Han; Jundong Zhu; Bing Xie; Yinglong Su; Shuai Zhou (Environmental Research, 2024)

Current applications and future impact of machine learning in emerging contaminants: A review - Lang Lei; Ruirui Pang; Zhibang Han; Dong Wu; Bing Xie; Yinglong Su (Critical Reviews in Environmental Science and Technology, 2023)

The crystalline structure transition and hydrogen bonds shift determining enhanced enzymatic digestibility of cellulose treated by ultrasonication - Boqun Shao; Zhibang Han; Ruirui Pang; Dong Wu; Bing Xie; Yinglong Su (Science of The Total Environment, 2023)

The role of pretreatments in handling antibiotic resistance genes in anaerobic sludge digestion – A review - Zhibang Han; Boqun Shao; Lang Lei; Ruirui Pang; Dong Wu; Jun Tai; Bing Xie; Yinglong Su (Science of The Total Environment, 2023)

The co-occurrent microplastics and nano-CuO showed antagonistic inhibitory effects on bacterial denitrification: Interaction of pollutants and regulations on functional genes - Ruirui Pang; Boqun Shao; Qiqing Chen; Huahong Shi; Bing Xie; Mostafa Soliman; Jun Tai; Yinglong Su (Science of The Total Environment, 2023)

Preparation of in-situ nitrogen-doped lignin-based porous carbon and its efficient adsorption of chloramphenicol in water - Aixia Chen; Yixuan Zhang; Xiao Wei; Jiaju Pang; Ruirui Hu; Juanjuan Guan (Environmental Science and Pollution Research, 2022)